(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This research aims to apply Dialogue Ethics (DE) to human resources in the tourist industry for the development of the Tourist guiding profession (TG.p) in tourist companies within the holy province of Karbala. The research problem stems from several inquiries concerning the understanding of the relational and influential nature of field variables. The study employed Habermes’s scale (1996) to measure dialogue ethics across three dimensions (Clarity (Pr), Integrity (CL), Honesty (HO)). The dependent variable was measured as the Tourist guiding profession in a unidimensional manner through a 10-item scale. The primary data collection tool was a questionnaire, and the sample included 115 managers from tourist companies in Karbala. The researcher determined the required sample size using the Herbert Arkin equation, resulting in a sample of 88 managers. Data analysis and processing were conducted statistically using Structural Equation Modeling, confirmatory factor analysis, descriptive scales, Pearson correlation coefficient, and simple linear regression analysis with statistical software including SPSS, Amos (Version 26). Statistical analysis results demonstrated a significant and meaningful impact of dialogue ethics on the development of the Tourist guiding profession. The results indicated a progression in the influence of the dimensions of dialogue ethics, starting with Clarity (Pr), followed by Honesty (HO), and finally, Integrity (CL), in terms of impact on the development of the Tourist guiding profession in tourist companies within the holy province of Karbala.